Efficiency of the system of operation of airborne radio technical means - Мелкумян, В. Г. (Proceedings of National Aviation University, 2002)
One of the approaches to assessing the efficiency of the system of operation of airborne radio technical means with the use of a technical and economic criterion of specific operating costs (average risk), with consideration of costs, aimed at maintaining and restoring the required level of quality of system operation, and costs in case of violation of the regularity of flights is considered. When selecting and implementing new systems due to the lack of statistical data that affect the efficiency of use in the system, it is proposed to solve the problem based on expert estimates using the theory of fuzzy sets.